MEMERANGI KEMISKINAN MELALUI PARTISIPASI PENDIDIKAN DAN AIR BERSIH PADA KABUPATEN DAN KOTA DI INDONESIA - Sidik Budiono; John Tampil Purb (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
The purpose of this study is togive the alternative solution to the regime about the new model of extention that increased literacy, education participation, and access to clean water in reducing poverty disparities.The methodology used was an econometric approach with a multiple regression equation model with robustness provisions. The data analyzed in this study covered 501 districts and cities throughout Indonesia in 2018. The calculation results prove that the model has been robust and all variables selected have a significant effect on the degree of freedom of 5% for all districts and cities in Indonesia. The results of this study suggest that education policy priorities, the avail-ability of clean water and adequate distribution are needed to reduce the poverty gaps.